An Empirical Survey on Basic Football Skills Among 10–13-Year-Old Athletes of Tanjung Balai United Football School - Simamora, Novembro; Winata, Devi Catur (Journal of Football Research, 2025)
Football serves as a fundamental medium for developing children’s motor and coordination skills. However, young athletes often focus more on playing than on mastering essential techniques, leading to suboptimal skill development. This study aimed to empirically examine the basic football skill levels of 10–13-year-old athletes at the Tanjung Balai United Football School (SSB) in 2022. Employing a quantitative descriptive design, data were collected through a survey method with standardized tests and measurements. Twenty male athletes aged 10–13 years participated in this study. The instrument utilized was the Football Skills Test for Ages 10–13 developed by Daral Fauzi (2009), with a validity coefficient of 0.98. Data were analyzed statistically and presented in percentage form. Findings revealed that 0% of the participants were in the very poor category, 42.4% in the poor category, and 57.6% in the moderate category, with none achieving good or very good classifications. These results indicate that the overall basic football skills of the athletes fall into the moderate level. The study underscores the importance of structured and consistent training programs to improve fundamental football skills at an early developmental stage.